On the existence of connected components of dimension one in the branch locus of moduli spaces of riemann surfaces - Costa, Antonio F.; Izquierdo, Milagros (Mathematica Scandinavica, 2012)
Let $g$ be an integer $≥3$ and let $B_{g}=\{X\in\mathcal{M}_{g}: Aut(X) eq Id\}$ be the branch locus of $M_{g}$, where $M_{g}$ denotes the moduli space of compact Riemann surfaces of genus $g$. The structure of $B_{g}$ is of substantial interest because $B_{g}$ corresponds to the singularities of the action of the modular group on the Teichmüller space of surfaces of genus $g$ (see [14]). Kulkarni ([15], see also [13]) proved the existence of isolated points in the branch loci of the moduli spaces of Riemann surfaces. In this work we study the isolated connected components of dimension 1 in such loci. These isolated components of dimension one appear if the genus is $g=p-1$ with $p$ prime $≥11$. We use uniformization by Fuchsian groups and the equisymmetric stratification of the branch loci.